Effect of 38% carbamide peroxide on the microleakage of silorane-based versus methacrylate-based composite restorations - Sedighe Sadat Hashemi Kamangar; Maryam Ghavam; Nazanin Mahinfar; Seyed Jalal Pourhashemi (Korean Academy of Conservative Dentistry, 2014)
Objectives This study aimed to assess the effect of 38% carbamide peroxide on the microleakage of class V cavities restored with either a silorane-based composite or two methacrylate-based composites. Materials and Methods A total of 96 class V cavities were prepared on the buccal surface of extracted human teeth with both enamel and dentin margins and were randomly assigned into three groups of Filtek P90 (3M-ESPE) + P90 system adhesive (3M-ESPE)(group A), Filtek Z250 (3M-ESPE) + Adper Prompt L-Pop (3M-ESPE)(group B) and Filtek Z350XT (3M-ESPE) + Adper Prompt L-Pop (group C). Half of the teeth were randomly underwent bleaching (38% carbamide peroxide, Day White, Discus Dental, applying for 15 min, twice a day for 14 day) while the remaining half (control) were not bleached. Dye penetration was measured following immersion in basic fuchsine. Data were statistically analyzed using Kruskal-Wallis and Mann-Whitney U tests at a level of 0.05. Results No significant differences were found between composites in the control groups in enamel (p = 0.171) or dentin (p = 0.094) margins. After bleaching, microleakage of Z250 (in enamel [p = 0.867] or dentin [p = 0.590] margins) and Z350 (in enamel [p = 0.445] or dentin [p = 0.591] margins) did not change significantly, but the microleakage of P90 significantly increased in both enamel (p = 0.042) and dentin (p = 0.002) margins. Conclusions No significant differences were noted between the bleached and control subgroups of two methacrylate-based composites in enamel or dentin margins. Microleakage of silorane-based composite significantly increased after bleaching.